THE RELATIONSHIP BETWEEN VALUE ORIENTATIONS AND THE EMOTIONAL COMPONENT OF READINESS FOR MARRIAGE OF YOUNG WOMEN - Лич, Оксана; Косс, Анна (SWorldJournal, 2024)
The article proposes to consider the relationship between the value orientations of young women and their readiness for marriage. The very concept of readiness for marriage is multicomponent, and we have singled out the emotional component of this interna